PENYERAPAN UAP AIR PADA BAHAN KOMPOSIT CARBON / EPOXY - Hadi, Bambang Kismono; Jupriyanto, Jupriyanto; Rusnaedi, Edi (Mesin, 1997)
In this paper, moisture absorption process in composite material was analytically and experimentally studied. The environmental condition was 72o C and 85 % RH. During a fixed interval time, the composite specimens were taken out from the experimental chamber and weighted. The weight gain showed that the absorption isoterm proï¬le followed Fick Law andthere was a good agreement between the analytical and experimental results. The average maximum moisture absorption was 0.84 %.